2022
DOI: 10.1002/aoc.6631
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in synthesis of quinazoline‐2,4(1H,3H)‐diones: Versatile building blocks in N‐heterocyclic compounds

Abstract: Quinazoline-2,4(1H,3H)-dione is a significant class of N-fused heterocyclic with a wide range of biological functions, including anti-HIV, anticancer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 148 publications
0
5
0
Order By: Relevance
“…Then, the conditions search for the implementation of the cyclocondensation was performed. Since the occurrence of similar reactions under basic conditions is described in the literature [50,69], we tested several bases and t-BuONa gave the best results. Having chosen the conditions for the cyclocondensation of the intermediate urea 7, we synthesized thienopyrimidine-2,4-diones 8a-f in the overall yield of 35-56% according to the two-stage one-pot procedure (Scheme 7).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Then, the conditions search for the implementation of the cyclocondensation was performed. Since the occurrence of similar reactions under basic conditions is described in the literature [50,69], we tested several bases and t-BuONa gave the best results. Having chosen the conditions for the cyclocondensation of the intermediate urea 7, we synthesized thienopyrimidine-2,4-diones 8a-f in the overall yield of 35-56% according to the two-stage one-pot procedure (Scheme 7).…”
Section: Resultsmentioning
confidence: 94%
“…Among the quinazoline and thienopyrimidine diones described in the literature, most of the compounds contain a substituent in position 3. The biological significance causes the emergence of a number of methods for the synthesis of 3-substituted quinazoline-2,4diones, including (i) the treatment of 2-aminobenzamides with phosgene, (ii) the reaction of isatoic anhydride with amines or isocyanates, (iii) the condensation of 2-halobenzoates with monoalkylureas, (iv) Baeyer-Villiger oxidation of 4-iminoisatins, (v) the three-component catalytic condensation of 2-haloanilines with CO 2 and isocyanides (Scheme 1) [49,50]. Instead of phosgene, various phosgene surrogates can be used as a carbonylating agent, including phenylisocyanate [51] or Troc-group [52].…”
Section: Introductionmentioning
confidence: 99%
“…H-bonds with other substances and properties such as amphipathy and acid–base make them excellent catalysts in the reaction process. 197,198 IL-based catalysts provide numerous benefits compared with traditional catalysts, such as their high adjustability and recyclability, reduced metal and halogen pollution, and enhanced separation between the catalyst and the product. In addition, IL-based catalytic systems offer a notable advantage in terms of reducing neutralization after the reaction, thereby enhancing their sustainability.…”
Section: Biomedical Aidsmentioning
confidence: 99%
“…There are several review articles that have been published for the synthesis of quinazoline-2,4(1 H ,3 H )-diones from CO 2 and o -aminobenzonitriles. Gheidari and Mehrdad et al [ 26 ] have reviewed the recent advances in synthesis of quinazoline-2,4(1 H ,3 H )-diones. Soleimani-Amiri et al [ 27 ] and Zhu et al [ 28 ] have reported the mechanisms and reaction conditions of CO 2 with o -aminobenzonitrile for the synthesis of quinazoline-2,4-dione.…”
Section: Introductionmentioning
confidence: 99%